2020
DOI: 10.1177/1747021820940300
|View full text |Cite
|
Sign up to set email alerts
|

The self-defining period in autobiographical memory: Evidence from a long-running radio show

Abstract: This study is the first to demonstrate that a self-defining period (SP) for personally relevant music emerges spontaneously in a public naturalistic setting. While previous research has demonstrated that people tend to have better memory and preference for songs from their teenage years, the theoretical relevance of these studies has been limited by their reliance on forced-choice methodology and a confinement to contemporary popular Western music. Here, we examine the record choices of famous guests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…As word-cued memories were also retrieved faster, this indicates that word cues were able to directly isolate more specific episodes from one's autobiographical memory store than music 4 . This aligns with previous findings that music tends to bring back memories of time periods and extended/repeated events more often than specific events (Baird et al, 2018;Janata et al, 2007;Loveday et al, 2020). Mazzoni et al (2014) found that both complex and simple pictorial cues elicited fewer 4 See also previous research demonstrating that more involuntarily retrieved memories are recalled faster and are more specific (Berntsen et al, 2013;Bernsten & Hall, 2004;Schlagman & Kvavilashvili, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…As word-cued memories were also retrieved faster, this indicates that word cues were able to directly isolate more specific episodes from one's autobiographical memory store than music 4 . This aligns with previous findings that music tends to bring back memories of time periods and extended/repeated events more often than specific events (Baird et al, 2018;Janata et al, 2007;Loveday et al, 2020). Mazzoni et al (2014) found that both complex and simple pictorial cues elicited fewer 4 See also previous research demonstrating that more involuntarily retrieved memories are recalled faster and are more specific (Berntsen et al, 2013;Bernsten & Hall, 2004;Schlagman & Kvavilashvili, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…The link between music, memory, and autobiography is investigated through the lens of identity, in keeping with the assertion that ‘both memory and self are constructed through specific forms of social interactions and/or cultural frameworks that lead to the formation of an autobiographical narrative’ (Fivush & Haden, 2003, p. xii). Our focus on youth is motivated by the analytical fertility of the ‘reminiscence bump’ (Rubin et al, 1986), a concept recently re-assessed by Loveday et al (2020) in terms of the ‘self-defining period’ (SP) to better account for ‘the main theoretical aspect of memories from the SP, which is their enduring relation to self across the lifespan ’ (p. 1; our italics). Autobiography, memory, and identity are co-constitutive: by exploring the way we interpret the effects of meaningful musical experiences on our past-and-present identities, we can better understand their autobiographical significance and the types of memories they engender.…”
Section: Introductionmentioning
confidence: 99%
“…For this book, we have been able to drill down into our survey data in greater detail by working alongside our colleague Professor Catherine Loveday, a neuropsychologist who has written extensively on music and memory (Alexomanolaki, Loveday and Kennett, 2006;Alexomanolaki, Kennett and Loveday, 2010;Loveday, Woy and Conway, 2020). When we break our data down by specific occupation, we can see that when we isolate artists (defined in our survey responses as adhering to either the category of musician, solo artist, songwriter or DJ, and highlighted in bold below) then levels of selfreported anxiety and depression are significantly higher than for more broadly defined music industry workers (defined in survey responses as adhering to either the category of live crew, audio production, publisher, management or other).…”
Section: A Deep Dive: Solo Artists Gender and Agementioning
confidence: 99%